Cesium radioactivity in peripheral blood is linearly correlated to that in skeletal muscle: Analyses of cattle within the evacuation zone of the Fukushima Daiichi Nuclear Power Plant. (30th November 2014) - Fukuda, Tomokazu; Kino, Yasushi; Abe, Yasuyuki; Yamashiro, Hideaki; Kobayashi, Jin; Shimizu, Yoshinaka; Takahashi, Atsushi; Suzuki, Toshihiko; Chiba, Mirei; Takahashi, Shintaro; Inoue, Kazuya; Kuwahara, Yoshikazu; et al.
Abstract The accident at the Fukushima Daiichi Nuclear Power Plant (FNPP) released a large amount of radioactive substances into the environment. Furthermore, beef contaminated with radioactive cesium above the 500 Bq/kg safety standard was circulated in the food chain in 2011. Japanese consumers remain concerned about the safety of radioactively contaminated food. In our previous study, we detected a linear correlation between radioactive cesium (137Cs) activity in blood and muscle around 500 to 2500 Bq/kg in cattle. However, it was unclear whether the correlation was maintained at a lower radioactivity close to the current safety standard of 100 Bq/kg. In this study, we evaluated 17 cattle in the FNPP evacuation zone that had a 137Cs blood level less than 10 Bq/kg. The results showed a linear correlation between blood 137Cs and muscle 137Cs (Y = 28.0X, R2 = 0.590) at low radioactivity concentration, indicating that cesium radioactivity in the muscle can be estimated from blood radioactivity. This technique would be useful in detecting high‐risk cattle before they enter the market, and will contribute to food safety.